RISIKO DAN MANAJEMEN RISIKO TERHADAP KECURANGAN PENGENDALIAN DAN AKUNTANSI MANAJEMEN - Christina Verawati Situmorang; Duma Megaria Elisabeth; Arthur Simanjuntak (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
Recent global events, particularly the global financial crisis, have renewed and strengthened interest in risk and the types of systems used to manage it. One area that has received relatively little attention is risk, risk management, and the interrelationships between managerial accounting and management practices. The methodology used in this research is library research. Processes related to the relationship between observed phenomena to the dynamics of the relationship, always use scientific logic. Although the data source for this research is a secondary data source consisting of significant previous scientific research articles in the form of books and other scientific works containing different perspectives. This research provides an introduction to risk in management accounting and control and a special edition of the Journal of Risk Management. It is argued that risks and how they are managed have become a hallmark of organizational life in both the public and private sectors. By changing organizational practices, risk management can facilitate and justify certain types of organizations. It can change the boundaries of responsibility and accountability in an organization by representing a certain way of organizing individuals and activities. In addition, it is said that risk management is a major issue because it has moved from a purely financial issue (risk assessment, derivatives, etc.) or accounting (financial report disclosure, etc.) to one of business controls. An area where management accounting should be involved. This article also examines the potential side effects of risk management, including issues of trust and accountability, but also focuses on managing secondary or defensive risks and reputational risks that arise.